Oceny zachowań komunikacyjnych w wypowiedziach przed Trybunałem Stanu w sprawie Gabriela Czechowicza w latach 1928-1930 = Evaluation of communication behaviour in statements before the State Tribunal in the case of Gabriel Czechowicz, 1928-1930 - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the presented analysis is to show and interpret the use of words and expressions that determine the quality of interlocutors` statements to an arbitrator as the State Tribunal is. The research material covered a collection of documents, mainly forensic statements and witness testimony in a trial, published in the 1961 collective issue. It is clear that the basic argument to prove or refute a charge in a court case is to prove speech, testimony of untruth.
Keywords: retoryka; przemówienie sądowe; argumentacja; 20 w.; rhetoric; court speech; argumentation